Organic Solid Waste Management by Producing Eco-Enzymes from Fruit Skin in Permata Tembalang - Budi Prasetyo Samadikun; Sudarno Sudarno; Yustina Metanoia Pusparizkita; Nurandani Hardyanti; Fathan Syahreza Pratama; Rahayu Puji Safitri (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2023)
The Ministry of Environment and Forestry in 2020 estimates that waste dumps in Indonesia will be 67.8 million tons. However, organic waste management in Indonesia is still relatively low. The accumulation of organic waste in the landfill, which usually causes unpleasant odors and potentially cause an explosion due to the production of methane gas from natural decomposition processes, can be avoided by prioritizing waste management from the source. An alternative way to handle organic waste is make eco-enzymes because it is efficient, economical, and environmentally friendly. This is the focus of the community service team. The community service method is carried out in three stages, including the preparation stage, the implementation stage, and the final stage. The preparation stage consists of doing a module for sorting organic waste and its utilization (making eco-enzymes). The next phase consists of socialization, education, and training on sorting organic waste and making the right eco-enzymes. The final stage consists of evaluation and making a final report. The expected result after education, socialization, or training has been carried out by the community service team, the community members, especially RT 04      RW 05 Permata Tembalang, know better and understand the sorting and utilization of organic waste.